Analisis Laporan Keuangan Sebagai Alat dntuk Menilai Kinerja Keuangan Perusahaan pada PT. Jasa Marga (Persero) TBK Tahun 2021 - 2024 - Nurul Ghefira; Dalizanolo Hulu (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to evaluate the financial performance of PT Jasa Marga (Persero) Tbk during the period 2021 to 2024 in an effort to assess the effectiveness of financial management within the infrastructure sector. The main focus of the study is to determine whether there has been an improvement in financial performance based on relevant financial indicators. The analysis was conducted using a descriptive quantitative approach based on the company’s published annual financial statements. The results indicate that, in general, PT Jasa Marga has experienced a significant improvement in financial performance over the past four years. This is reflected in improved liquidity, solvency, profitability, and activity ratios. The increase in toll revenue, as the company’s main source of income, along with profit growth and operational efficiency, serve as key indicators of the success of management strategies in addressing post-pandemic challenges and expanding national toll road projects. Additionally, improved debt management is evidenced by the declining leverage ratios year after year. These findings support the hypothesis that there has been an improvement in financial performance during the observation period.